Mining for Salt in European Prehistory - Harding, Anthony (Archaeopress Archaeology, 2018)
Salt was produced in a number of ways in ancient times. Evaporation using briquetage was the commonest, but mining or quarrying rock salt is better known, especially from the famous mines at Hallstatt (Gmunden district) and the Dürrnberg (Hallein district). One of the richest areas for salt is the Carpathian zone; the article describes the results of recent fieldwork in Romania, where a technique using wooden troughs and wattle-framed ponds was used. It is argued that a form of open-cast mining was employed, the troughs used to assist breaking up the rock salt surface, and perhaps also to facilitate concentration of brine
il. ; 29 cm